The Influence of Education on The Knowledge and Attitudes of Teenage Girls About Early Pregnancy - Yenny Aulya; Retno Widowati; Shervy; Bunga Tiara Carolin (International Journal of Midwifery and Health Sciences, 2025)
Pregnancy is a time when a woman carries a fetus embryo in her body. Early pregnancy is a pregnancy that occurs at the age of less than 20 years. Data shows that teenage pregnancy is related to low levels of education and economic status. Lack of knowledge about reproductive health contributes to the high rate of unwanted pregnancies. This study aims to determine the effect of education on the knowledge and attitudes of teenage girls about early pregnancy at SMK Grafika De.sa Pute.ra South Jakarta. This study aims to determine the effect of education on the knowledge and attitudes of teenage girls about early pregnancy at SMK Grafika Desa Putera South Jakarta. The results of the study showed a significant influence on the knowledge and attitudes of adolescent girls after being given early pregnancy education with a Sig value <0.001. Providing education increases the knowledge and attitudes of adolescent girls about early pregnancy.